2009
DOI: 10.1161/circresaha.109.197277
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Na + Current Regulation by Pyridine Nucleotides

Abstract: Rationale: Mutations in glycerol-3-phosphate dehydrogenase 1-like (GPD1-L) protein reduce cardiac Na ؉ current (I Na ) and cause Brugada Syndrome (BrS). GPD1-L has >80% amino acid homology with glycerol-3-phosphate dehydrogenase, which is involved in NAD-dependent energy metabolism.Objective: Therefore, we tested whether NAD(H) could regulate human cardiac sodium channels (Na v 1.5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
141
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 55 publications
4
141
0
1
Order By: Relevance
“…The observation of NADH-induced ROS production in our study is consistent with others (27)(28)(29)(37)(38)(39). However, the mechanism is not well understood.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The observation of NADH-induced ROS production in our study is consistent with others (27)(28)(29)(37)(38)(39). However, the mechanism is not well understood.…”
Section: Discussionsupporting
confidence: 87%
“…Alterations in NADH/NAD ϩ ratio not only reflect abnormal redox and metabolic conditions but can also play a primary role in the regulation of ion channels. Recent studies demonstrated that NADH inhibits the Na ϩ current (27,28) and increases spontaneous SR Ca 2ϩ release (29) in cardiomyocytes. A sustained elevation of cytosolic NADH can occur under ischemic or hypoxic conditions, which was mimicked in this work by raising cytoplasmic NADH via the patch pipette or by increasing the NADH/NAD ϩ redox potential with lactate treatment, leading to a marked inhibition of I NCX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter gene defect has been suggested to cause suppression of the Na + current by a PKC-dependent mechanism that is linked with the redox state of the cell (103,104). Specifically, reduced enzymatic activity of mutant GPD1L is associated with an NADH/NAD + imbalance that can activate protein kinase C and lead to phosphorylation of a specific serine residue (Ser1503) on Na V 1.5, causing reduced channel activity.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, mutations in the gene encoding glycerol-3-phosphate dehydrogenase 1-like protein (GPD1L), which cause Brugada syndrome and sudden infant death syndrome, have been shown to reduce SCN5A current (24,34). Recent studies (24,33) have implicated the downregulation of cell surface Na ϩ channels by PKC activation as the likely mechanism for this effect, although other data have suggested that the mechanism may be more complex (23). These data regarding GPD1L mutations further support a clinically important role for PKC-mediated regulation of cardiac I Na in the generation of serious cardiac arrhythmias.…”
mentioning
confidence: 99%